Sustainable Development Concept As A Prerequisite For Society Development In A Globalized World - Клешня, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. Globalized processes and scale structural social changes caused the necessity of solving of modern global problems implying the future strategy of development of both separate states and the worlds as a whole. It causes the aim of the study: to analyze the agenda and goals of sustainable development. There are the tasks to find out the gaps in the existing strategy and to develop the proposals for discussion and extension of update goals of the sustainable development. Research methods: the socio-cultural and comparative methodological approaches in their dialectical unity were used in the study to unfold the essence of the axiological grounds of the modern globalized society for their comparison. Research results: the unique feature of the sustainable development concept is its role as a methodological and normative resource for the society’s development. This concept has emerged in the context of the needs of solving global environmental problems, overcoming the environmental crisis, which is recognized by the global community. However, the implementation of the sustainable development concept has faced a number of contradictions. It is becoming even more apparent that the solutions proposed by scholars have proved to be extremely inconvenient for the capitalist system for both subjective and objective reasons. To realize sustainable development concept, the market system is forced to overcome, to a degree, itself. Discussion. The global ecological crisis is a spiritual rather than the material problem, above all, it is caused by the state of consciousness of contemporary man itself. The environmental problem is a vexatious and threatening result of Homo sapiens’ activities, whose value picture of the world is within the ideology of the consumption society. Conclusions. A civilization based on a materialist worldview that reflects only one side of a single world – unlimited consumption driven by continuous development, cannot survive. This position is contrary to physical laws, since it requires unlimited resources. Therefore, it needs a thorough revision. Revision, refinement and enlargement need not only the basic goals of sustainable development, which should become the ideological guideline of today’s global community. They need detailed elaboration and philosophical justification as the basis of the new social and ecological worldview of the mankind, as well as the ways of its formation, etc.